Association between promoter methylation and gene expression of CGB3 and NOP56 in HPV‑infected cervical cancer cells. Issue 1 (20th October 2021) - SINGH, PALAK; CHALERTPET, KANWALAT; SUKBHATTEE, JUTHAMARD; WONGMANEE, NANNABHAT; SUWANNAKART, PIMWIPA; YANATATSANEEJIT, PATTAMAWADEE
No abstract available